PENGARUH KUALITAS PRODUK DAN PROMOSI TER HADAP KEPUTUSAN PEMBELIAN KERUPUK KULIT SAPI “CITRA SARI” DI DESA CIBURIAL KEC. CIMENYAN - Zeffanya Raphael Wijaya; Hasti Pramesti Kusnara; Cucu Hodijah (Media Bina Ilmiah, 2023)
Companies can still compete in the market if in issuing products tailored to the needs and desires of consumers, then communicating the advantages of the product to consumers. A consumer in making a decision to purchase a product can be influenced by several factors, including the quality of the product and the promotions carried out by the company. Referring to this fact, the researcher is interested in conducting research on "The Influence of Product Quality and Promotion on the Purchase Decision of "CITRA SARI" cowhide crackers in CIBURIAL VILLAGE, KEC. CIMENYAN". The problems studied in this study are: (1) Is there any influence of product quality on purchasing decisions of "CITRA SARI" cowhide crackers in CIBURIAL VILLAGE, KEC. CIMENYAN ? (2) Is there any effect of promotion on purchasing decisions of "CITRA SARI" cowhide crackers in CIBURIAL VILLAGE, KEC. CIMENYAN ? (3) Is there any influence between product quality and promotion simultaneously on the purchasing decision of "CITRA SARI" cowhide crackers in CIBURIAL VILLAGE, KEC. CIMENYAN? The methods used in data collection are the questionnaire method (questionnaire) and the documentation method. The data analysis method used in this study is Multiple Linear Regression Analysis which is used to determine the effect of the independent variable and the dependent variable,namely product quality (X1) and promotion (X2) on purchasing decisions (Y). By using the SPSS program, it can be obtained Fcount of 12,449 > Ftable 3.09 with a significance level of 5%, so that the alternative hypothesis (Ha) is accepted, namely that there is a positive influence between product quality and promotion on the purchasing decision of "CITRA SARI" cowhide crackers in CIBURIAL VILLAGE, KEC . CIMENYAN. The conclusion of the research is that there is a positive influence between product quality and promotion on purchasing decisions of "CITRA SARI" cowhide crackers in CIBURIAL VILLAGE, KEC. CIMENYAN. The magnitude of the influence of product quality on purchasing decisions can be seen from the coefficient of determination, which is 0.316. This means that partially the product quality factor influences the purchasing decision by 31.6%. While the coefficient of determination for the promotion variable is 0.128. This means that partially the promotion factor has an effect on purchasing decisions by 12.8%. Based on these results, researchers provide suggestions that producers must be able to maintain product quality so that the resulting product remains an option for consumers. In addition, companies must further improve promotional programs so that promotional activities are carried out more effectively, because promotions function to influence consumer attitudes and preferences in choosing products, as well as to motivate consumers to take positive action, namely making purchase decisions on the products offered.